Linking Structured Data - Hausenblas, Michael; Kerrin, Michael; Pizzo, Michael; Viegas, Evelyne; Wilson, Neil (Microsoft Research, 2013)
This whitepaper explores how OData can be used to expose data within an RDF triple store through an end-user oriented model, and consumed by a broad range of consumer-oriented tools and applications. In order to better understand how RDF data could be exposed and consumed by OData clients in a real world example, we went from theory to practice by focusing on some scenarios from the British Library which publishes its metadata on the Web according to the Linked Data principles. As of today there are not many common tools and consumer-oriented applications to browse, query, and analyze this RDF-based data. It is exactly this limitation that this paper tries to overcome by allowing rich and integrated development environments to directly import and/or access the RDF-based Linked Data.